INVESTIGATING THE ACCURACY OF AN UPGRADED TRANSCUTANEOUS BILIRUBIN SCREENING TOOL BY SITE OF TESTING - Jegathesan, T (Paediatr Child Health, 2017)
BACKGROUND: Severe neonatal hyperbilirubinemia continues to occur in healthy term infants. The incidence has decreased as a result of guidelines by the Canadian Pediatric Society (CPS) and American Academy of Pediatrics (AAP), requiring all healthy newborns to receive either a transcutaneous bilirubin (TCB) or total serum bilirubin (TSB) at discharge. Several studies have investigated the effectiveness of TCB tools. However, discrepancies still exist on the agreement between TCB and TSB by site and treatment. OBJECTIVES: The aim of this study was to determine the accuracy and agreement of TCB and TSB by site and treatment using the JM-105. DESIGN/METHODS: A multi-site prospective clinical trial of term infants requiring TSB measurements. Pearson’s correlation coefficient was used to determine the accuracy between TSB and TCB measurements by site and treatment. Bland-Altman Plots of the agreement between TSB and TCB values by site and treatment were generated. RESULTS: Paired TSB and TCB measurements from the forehead and sternum were collected from 75 term infants between 36-44 weeks gestational age. Bland-Altman Plots by site demonstrated the mean difference between TSB and TCB on the forehead to be -1.72 μmol/L ± 24.64 μmol/L (-66.7 μmol/L to 49.00 μmol/L) and sternum to be 1.2 μmol/L ± 37.99 μmol/L (-82.00. μmol/L to 136.33 μmol/L). The mean TSB level was 131.43 μmol/L ± 54.88 μmol/L (31 μmol/L – 285 μmol/L), mean TCB level on the forehead was 132.40 μmol/L ±57.029 μmol/L,(19 μmol/L-284.5 μmol/L) and mean TCB level on the sternum was 121.32 μmol/L ±58.27 μmol/L, (13.5 μmol/L-261.6 μmol/L). Paired t-tests revealed no significant mean differences between TCB and TSB measurements by site and treatment. The correlation between the TSB and TCB values from the forehead (Pearson’s correlation r =0.877, p<0.01) were higher than the correlation between TSB and TCB values from the sternum (r= 0.646, p<0.01). The correlation between TSB and TCB values on the forehead (r=0.879, p<0.01) and sternum (r=0.747, p<0.01) were higher prior to phototherapy. The mean difference between TSB and TCB after phototherapy on the forehead was 25.77 μmol/L ± 48.36 μmol/L and sternum was 95.69 μmol/L ± 73.72 μmol/L. CONCLUSION: The JM-105 is an accurate TCB screening tool for physicians to use in healthy newborns by site. After the initiation of phototherapy the forehead may be a more appropriate site of measure with an overestimate of bilirubin levels. Additional research is required to obtain a greater understanding of the impact of phototherapy and site on TCB screening tools.